2015
DOI: 10.1097/mrr.0000000000000088
|View full text |Cite
|
Sign up to set email alerts
|

Cross-cultural adaptation, validation, and reliability testing of the Shoulder Pain and Disability Index in the Persian population with shoulder problems

Abstract: level II.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
25
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 10 publications
3
25
0
Order By: Relevance
“…These authors did not find any significant problems and/or difficulties in the cross-cultural adaptation process. The lack of difficulties in comprehension for the participants during the cross-cultural process is consistent with other studies [ 17 , 28 , 29 ]. Moreover, our new Spanish language version achieved good readability.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…These authors did not find any significant problems and/or difficulties in the cross-cultural adaptation process. The lack of difficulties in comprehension for the participants during the cross-cultural process is consistent with other studies [ 17 , 28 , 29 ]. Moreover, our new Spanish language version achieved good readability.…”
Section: Discussionsupporting
confidence: 91%
“…Similar to other cross-cultural studies on SPADI [ 30 32 ], we found a strong correlation between the SPADI and the Quick-DASH indicating good convergent validity. Alsanawi et al [ 33 ] found a correlation between the SPADI and DASH of 0.84 (Spearman coefficient), while Ebrahimzadeh et al [ 28 ] reported a correlation of 0.61.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to those of prior validation studies, Persian version of modified ODQ was found to be valid and reliable for low back pain disability assessment in an Iranian population. For a patient centered tool, slight differences tailored for cultural adaptation are acceptable as far as the results prove to be valid and reliable [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…To answer the questions, subjects place a mark on a numbered scale ranging from "0 (for no pain and difficulty) to 10 (for maximum pain, or difficulty in function, so that the patient needs help)" for each question [30]. Validity and reliability of this questionnaire in Persian version has been confirmed in previous researches [31].…”
Section: Outcome Measuresmentioning
confidence: 56%